2010
DOI: 10.1016/j.ijdevneu.2010.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐ and/or postnatal protein restriction in rats impairs learning and motivation in male offspring

Abstract: Suboptimal developmental environments program offspring to lifelong health complications including affective and cognitive disorders. Little is known about the effects of suboptimal intrauterine environments on associative learning and motivational behavior. We hypothesized that maternal isocaloric low protein diet during pregnancy and lactation would impair offspring associative learning and motivation as measured by operant conditioning and the progressive ratio task, respectively. Control mothers were fed 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 61 publications
3
40
0
4
Order By: Relevance
“…Although our findings were more subtle, a stronger anxiety and/or depressive phenotype in MLP offspring in the CF1 strain of mice [14] and in the more commonly used rat model has been shown [15]. It is known that when comparing behavioral outcomes from different studies, the species and genetic background, as well as the content and exposure timing and length of the MLP diet can have dramatic effects on the severity of the behavioral phenotype of the offspring [2, 11, 13, 15].…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Although our findings were more subtle, a stronger anxiety and/or depressive phenotype in MLP offspring in the CF1 strain of mice [14] and in the more commonly used rat model has been shown [15]. It is known that when comparing behavioral outcomes from different studies, the species and genetic background, as well as the content and exposure timing and length of the MLP diet can have dramatic effects on the severity of the behavioral phenotype of the offspring [2, 11, 13, 15].…”
Section: Discussionmentioning
confidence: 93%
“…Studies have shown that dietary modifications during gestation can influence neurodevelopment in male [14, 15] and female [14] offspring, manifesting as behavioral changes. Therefore, we carried out a battery of neurobehavioral assays for anxiety, depression, repetitive behaviors, sociability, and learning and memory.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In regards to motivation for positive reinforcement, prenatally undernourished rats show less appetitive motivation (Miles et al, 2009). We also have reported less motivation in male rats following pre and/or postnatal protein restriction (10% casein) (Reyes‐Castro et al, 2011b).…”
Section: Introductionmentioning
confidence: 81%